(untitled) (Revista de Estudos da Linguagem, 1999)
The aim of this paper is to juxtapose the theme of missionaryliteracy with a theoretical discussion of the attribute of autonomywith reference to literacy. By missionary literacy we mean thealphabetic typographic writing system created by missionaries aspart of the evangelical process of biblical translation. In particular,this study focuses on those cases of missionary literacy based onlinguistics, for which the Summer Institute of Linguistics (SIL) is ofspecial significance.In so far as the debate on autonomy is concerned, we refer tothe controversy between the autonomy model of Goody, Ong andOlson and the ideological model of Street. The relevance of thequestion of autonomy in relation to the theme of missionary literacyhas its origins in the Protestant tradition, that the text is its owninterpreter (Olson 1991), an autonomous conception of the writtentext. This concept of literacy is a special expression of religiousliteral meaning, and therefore allows us to focus attention on theparticular feature of literacy in the missionary domain.